Ultrasound-Sensitive Liposomes for Triggered Macromolecular Drug Delivery: Formulation and In Vitro Characterization - de Matos, Maria B. C.; Deckers, Roel; van Elburg, Benjamin; Lajoinie, Guillaume; de Miranda, Bárbara S.; Versluis, Michel; Schiffelers, Raymond; Kok, Robbert J. (Frontiers in Pharmacology, 2019)
Mistletoe lectin-1 (ML1) is a nature-derived macromolecular cytotoxin that potently induces apoptosis in target cells. Non-specific cytotoxicity to normal cells is one of the major risks in its clinical application, and we therefore propose to encapsulate ML1 in a nanocarrier that can specifically release its cargo intratumorally, thus improving the efficacy to toxicity ratio of the cytotoxin. We investigated the encapsulation of ML1 in ultrasound-sensitive liposomes (USL) and studied its release by high-intensity focused ultrasound (HIFU). USL were prepared by entrapment of perfluorocarbon nanodroplets in pegylated liposomes. The liposomes were prepared with different DPPC/Cholesterol/DSPE-PEG2000 lipid molar ratios (60/20/20 for USL20; 60/30/10 for USL10; 65/30/5 for USL5) before combination with PFC nanoemulsions (composed of DPPC and perfluoropentane). When triggered with HIFU (peak negative pressure 2–24 MPa, frequency 1.3 MHz), PFC nanodroplets can undergo phase transition from liquid to gas thus rupturing the lipid bilayer of USL. Small unilamellar liposomes were obtained with appropriate polydispersity and stability. ML1 and the model protein horseradish peroxidase (HRP) were co-encapsulated with the PFC nanodroplets in USL, with 3% and 7% encapsulation efficiency for USL20 and USL10/USL5, respectively. Acoustic characterization experiments indicated that release is induced by cavitation. HIFU-triggered release of HRP from USL was investigated for optimization of liposomal composition and resulted in 80% triggered release for USL with USL10 (60/30/10) lipid composition. ML1 release from the final USL10 composition was also 80% for the same formulation and that the. Given its high stability, suitable release, and ultrasound sensitivity, USL10 encapsulating ML1 was further used to study released ML1 bioactivity against murine CT26 colon carcinoma cells. Confocal live-cell imaging demonstrated its functional activity regarding the interaction with the target cells. We furthermore demonstrated the cytotoxicity of the released ML1 (i.e., after USL were treated with HIFU). The potent cytotoxicity (IC50 400 ng/ml; free ML1 IC50 345 ng/ml) was compared to non-triggered USL loaded with ML1. Our study shows that USL in combination with HIFU hold promise as trigger-sensitive nanomedicines for local delivery of macromolecular cytotoxins.